EVALUASI PEMAHAMAN SISWA MAN 1 BANYUMAS TERHADAP ANCAMAN PHISHING, MALWARE, DAN EVIL TWIN PASCA SOSIALISASI - Alviendra Putra Setiawan; Aziz Saputra Ramadon; Isma Bela; Rizqi Gilang Saputra; Nihlatul Jannah; Darso (Abdi Jurnal Publikasi, 2026)
The growth of internet technology in Indonesia has been accompanied by a significant rise in cybercrimes, such as online fraud, phishing, and data breaches. High school students are a particularly vulnerable group due to their limited understanding of digital security. To mitigate these risks, a community service program featuring interactive digital security education was conducted for 10th-grade students at MAN 1 Banyumas on April 29, 2026, comprising three main stages: preparation, implementation, and evaluation. The material was presented through a combination of theory and illustrative practical demonstrations covering threats—such as phishing, "evil twin" Wi-Fi networks, and malware—as well as preventive measures. A mixed-methods approach was used for evaluation, incorporating post-test questionnaires and field observations. The event proceeded smoothly and was met with great enthusiasm by the 30 participating students. Overall evaluation results indicated that student understanding and performance fell into the following categories: "Very Good" (65%), "Good" (34%), and "Adequate" (1%). These findings demonstrate an improvement in digital literacy and a shift in student attitudes toward greater vigilance regarding fake networks and manipulative links, alongside an increased ability to implement preventive measures to protect devices from malware.